Validation and measurement invariance of the Langer mindfulness scale: the Turkish version - Uysal Saraç, Menekşe; Yıldırım, Yıldız; Eşici, Hasan; Büyüköztürk, Şener; Pagnini, Francesco; Langer, Ellen (Frontiers in Psychology, 2024)
Novel distinction drawing is an active process that characterizes mindfulness, which has been associated with an open, creative, and probabilistic mental state, as well as the ability to examine information from new perspectives. The literature review revealed a lack of measurement tools for assessing mindfulness from a social and cognitive perspective in Türkiye. In addition, the frequent use of the Langer Mindfulness Scale (LMS) in educational contexts and its adaptation into many languages highlights the need for a Turkish version of the scale. This study aims to validate the Turkish version of the 14-item LMS. The Turkish version’s factorial structure was tested using the results of confirmatory factor analysis (CFA), which confirmed a three-factor structure that included the engagement, novelty-producing, and novelty-seeking subscales. It was found that measurement invariance based on gender was provided by LMS scores. LMS Turkish version showed satisfying psychometric properties in terms of reliability. Additionally, convergent and discriminant validity were examined in this validation study to provide evidence for criterion-based validity. For this purpose, the relationships between Turkish LMS scores and variables such as positive and negative affect, openness to experiences, self-acceptance, self-defined humor, and health were analyzed. The results showed that self-defined humor, positive affect, openness to experience, and self-acceptance were significantly positively correlated with the Turkish LMS scores, while LMS scores exhibited a significant negative relationship with negative affect. These findings suggest that the Turkish version of the LMS, with its three dimensions, shows acceptable psychometric properties for assessing the state of mindfulness. The Turkish version of the LMS is expected to be used in socio-cognitive mindfulness research in the Turkish cultural context.